2017
DOI: 10.1128/genomea.00908-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Nectarine stem pitting-associated virus , Isolated from Prunus persica in Cheongdo County, South Korea

Abstract: We report here the first complete genome sequence of a South Korean isolate of Nectarine stem pitting-associated virus (NSPaV) from peach and compare it with previously described complete NSPaV genome sequences. The highest whole-genome nucleotide sequence identity was 95.3% with GenBank accession no. KT273409 (NSPaV) from the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…6A). Three NSPaV RdRp gene sequences from T02 grouped with isolate SK from a nectarine in South Korea 22 . Other sequences including RdRp and nearly complete genome sequences of the T01, T03, T04 NSPaV isolates were found to be closely related to isolate NSPaV/12P42 derived from a nectarine in the USA 5 , but three NSPaV RdRp gene sequences from T04 were not consistant, and the T04-1 sequence was detected as a recombinant.…”
Section: Resultsmentioning
confidence: 99%
“…6A). Three NSPaV RdRp gene sequences from T02 grouped with isolate SK from a nectarine in South Korea 22 . Other sequences including RdRp and nearly complete genome sequences of the T01, T03, T04 NSPaV isolates were found to be closely related to isolate NSPaV/12P42 derived from a nectarine in the USA 5 , but three NSPaV RdRp gene sequences from T04 were not consistant, and the T04-1 sequence was detected as a recombinant.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the present study, three Prunus-infecting luteoviruses had been described: nectarine stem pitting-associated virus (NSPaV) is the first luteovirus identified in peach (Prunus persica) by Bag et al in the USA in 2015 (Bag et al 2015). Since then, NSPaV was reported naturally to infect peach in China, Hungary, South Korea, Australia (Igori et al 2017a;Jo et al 2017;Krizbai et al 2017;Lu et al 2017), and in P. mume (Japanese apricot) in Japan (Candresse et al 2017). Furthermore, it has been experimentally shown that NSPaV can infect P. avium (sweet cherry) and P. tomentosa (Nanking cherry) (Villamor et al 2016).…”
Section: Maryam Khalilimentioning
confidence: 86%
“…ALV-1 and ARWV-1, identified from the United States, were confirmed to be co-infected with more than two other viruses in apple rootstocks in Korea (Lim et al, 2019). NSPaV, discovered from nectarine cultivars imported from France to California, was reported in Italy, China, South Korea, and Japan (Candresse et al, 2017;Igori et al, 2017a;Lu et al, 2017;Sorrentino et al, 2018). CVF, identified from The Czech Republic and Greece, was reported in Canada (James et al, 2019).…”
Section: Biology Progress After the Discovery Of New Fruit Tree Virusmentioning
confidence: 91%
“…AVCaV only infected one out of 39 varieties of apricot while identified, but was reported in four additional species (P. salicina, P. mume, P. domestica, and P. persica; Abou Kubaa et al, 2014; Kinoti et al, 2017). NSPaV was identified in nectarine trees and reported to infect peach and Japanese apricot trees (Candresse et al, 2017;Igori et al, 2017a;Lu et al, 2017;Sorrentino et al, 2018). A highly divergent South Korean (SK) isolate of ChALV, which was identified from sweet and sour cherry trees, was also reported in peach trees (Igori et al, 2017b).…”
Section: Biology Progress After the Discovery Of New Fruit Tree Virusmentioning
confidence: 99%